2016
DOI: 10.1073/pnas.1613195113
|View full text |Cite
|
Sign up to set email alerts
|

Increased burden of deleterious variants in essential genes in autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is a heterogeneous, highly heritable neurodevelopmental syndrome characterized by impaired social interaction, communication, and repetitive behavior. It is estimated that hundreds of genes contribute to ASD. We asked if genes with a strong effect on survival and fitness contribute to ASD risk. Human orthologs of genes with an essential role in pre-and postnatal development in the mouse [essential genes (EGs)] are enriched for disease genes and under strong purifying selection re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 65 publications
7
56
0
Order By: Relevance
“…Previously, human cell-essential genes have been analysed [16][17][18] in conjunction with lethal genes identified in the mouse 23 by either characterising a core set of essential genes at the intersection 14 or studying the union of the two 32 . In these studies, cellular essential genes were shown to have a nearly complete concordance with mouse lethal genes 19,23 .…”
Section: Cross-species Comparisons Divide Genes Into Functional Binsmentioning
confidence: 99%
“…Previously, human cell-essential genes have been analysed [16][17][18] in conjunction with lethal genes identified in the mouse 23 by either characterising a core set of essential genes at the intersection 14 or studying the union of the two 32 . In these studies, cellular essential genes were shown to have a nearly complete concordance with mouse lethal genes 19,23 .…”
Section: Cross-species Comparisons Divide Genes Into Functional Binsmentioning
confidence: 99%
“…Occasionally, the same subject could have slightly different IDs between studies: for example, Yuen et al (2015) uses "-" (dash), while Yuen et al (2017) uses "_" (underscore) in otherwise identical subject IDs from the same cohort. Another example is the omission of "p1" suffix, meant to indicate a proband, from a Simons Simplex Collection (SSC) family IDs in Iossifov et al [2012], Iossifov et al [2014], and Ji, Kember, Brown, and Bu can [2016]. We attempt to rectify such discrepancies during the curation stage.…”
Section: Variant Harmonizationmentioning
confidence: 99%
“…Both representations describe the same resulting genotype. The other three papers report just one of the contiguous SNVs each [Krupp et al, 2017]: C-> A; [Ji et al, 2016]; and [Satterstrom et al, 2019]: C->G). This complex variant can also be viewed directly in VariCarta at varicarta.msl.ubc.ca/variant?chr=5&start=134059281&stop=134059281. central SFARI Human Gene module contains information about human genes that have been associated with ASD, supporting information from scientific literature, and different kinds of genetic data sets that provide evidence for linking the genes to ASD and help categorize and score genes based on the strength of that evidence.…”
Section: Comparison To Similar Resourcesmentioning
confidence: 99%
“…It has now been well documented using several approaches that LGD GDMs in probands show enrichments for genes that are highly conserved/intolerant to LGD mutations. 11,44,45 We reasoned that missense PMMs relating to ASD risk could also show similar enrichments. We selected two intolerant gene sets, an updated set of essential genes (n ¼ 2,455) 34 and the recently published ExAC intolerant set (n ¼ 3,232).…”
Section: Evaluation Of Mutation Rates and Burden In Children With Asdmentioning
confidence: 99%